THE SYMBOLIC PREMISE IN NADIN AMIZAH'S ALBUM: A PEIRCEAN SEMIOTIC APPROACH - Lestari, Febrianti Dwi; Dzarna, Dzarna; Ali Vardani, Eka Nova (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study investigates the symbolic premises embedded in Nadin Amizah’s albums Selamat Ulang Tahun (2020) and Untuk Dunia, Cinta, dan Kotornya (2022) through Charles Sanders Peirce’s semiotic framework. Employing a descriptive qualitative design and Herbert Blumer’s theory of symbolic interactionism, the research explores how icons, indexes, and symbols construct meaning in Amizah’s lyrical narratives. Data were collected from song lyrics and analyzed using Peirce’s triadic model to identify the interplay between imaginative imagery, emotional indicators, and figurative expressions. The findings reveal that the albums articulate intertwined themes of maternal affection, identity formation, emotional struggle, and spiritual reconciliation. Iconic signs depict visual metaphors of personal experience, indexes mark emotional and social relationships, while symbolic signs convey abstract representations of self-reflection and existential awareness. Through the semiotic process, Amizah’s works transcend musical aesthetics, functioning as cultural texts that reflect Indonesian youth’s emotional and social realities. The study contributes to Indonesian music semiotics by demonstrating how symbolic premises in popular lyrics mediate personal meaning and collective experience within contemporary socio-cultural contexts.